If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -13 = 3y Reorder the terms: -13 + 10x = 3y Solving -13 + 10x = 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 10x = 13 + 3y Combine like terms: -13 + 13 = 0 0 + 10x = 13 + 3y 10x = 13 + 3y Divide each side by '10'. x = 1.3 + 0.3y Simplifying x = 1.3 + 0.3y
| 2(h-1)=-3(h+12)-11 | | 6-x/2=2 | | Fx=10x-5 | | 3x+x+5x=72 | | -5=n/9-4 | | 14x^2-116x+32=0 | | -15*x^2= | | 8x^6-27y^6=0 | | (3/8)*72 | | 45/6-3i | | 2(3a-5)+2a=70 | | 32-3h=5h+8 | | -13=5(1+4m)+2 | | -13x-12=-129 | | 5(3-2)+8=43 | | 2n-3n=0-5 | | v^2-2=98 | | x=x+40+2x-5+3x-17 | | (3-5x)2-3x=-61 | | 77/9=99/x | | 10x+9y=5z-8w | | 115+x=4x-41 | | 4x+-4x+-11=11 | | 5y=12-y | | 9/77=99/x | | 2x^2+19+4x^2-13=180 | | 5(x+4)=3x+2 | | 15-1/6=1/6n-1 | | 3m+2(m-n)-2(m+n)= | | p=2i+2wfori | | 11x-3-6x=6x-2 | | (2-6)3=5 |